Integrasi Low Power Sensor Node Berbasis Protokol Message Queue Telemetry Transport - Sensor Network (MQTT-SN) & ATmega328p - Muhammad Sabilillah; Sabriansyah Rizqika Akbar; Rakhmadhany Primananda (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
The technology of Wireless Sensor Network (WSN) can be used in a wide variety of needs for example in terms of its network of offices, companies, health care, and even daily activities that require the WSN. However, in terms of the functions that are owned by WSN technology required monitoring against resources consumed in order not going waste of resources. Meanwhile, on the other hand monitoring the transfer of certain activities require the existence of a state. For the problem of the excessive use of power resources in the intermediate implementation mechanism needed quite a long low power on sensor nodes in some conditions one of which was the sleep mode on a periodic basis. Taking and sending of data sensors this time using gas sensor MQ-7. Mikrokontroller used in the sensor node is system has low power features ATmega328p in its components. For the method used in protocol the MQTT-SN is mechanism of publish-subscribe communication serves as a regulator of event-driven architecture on each state. Protocol on the MQTT-SN has four state two of which also feature sleep available which are suitable for the application of energy-saving systems. After testing done on these results are obtained when the ATmega328p normal average current of 45.15 mA and when the sleep of 26.47 mA with the reduction of current of 18.68 mA.